Perancangan Sistem Manajemen Keselamatan dan Kesehatan Kerja di PT. Ridwan Jaya Agung. - Ferdi Wijaya; Kriswanto Widiawan (Jurnal Titra, 2021)
This thesis aims to create a design of occupational safety and health management system in PT. Ridwan Jaya Agung that in accordance with the Government Regulation Number 50 of 2012. The design of the system consists of several stages which are initial audit, interviews related to the company's capabilities, analysis of the company's initial gap, policy determination, design of K3 implementation, design of K3 monitoring, introduction of K3, and new audits. In the initial audit, the company could only fulfilled 1 out of 122 criteria; equivalent to 1%, which according to the Government Regulation is not a good or ideal auditing results. Therefore, through this thesis, the researcher had created a design of occupational safety and health management system that meets 119 criteria; equivalent to 98%, and can be said to have fulfilled the implementation of occupational safety and health management system.